POPULASI BEKANTAN Nasalis larvatus, WURM DI KAWASAN HUTAN SUNGAI KEPULUK DESA PEMATANG GADUNG KABUPATEN KETAPANG KALIMANTAN BARAT - Rizal, M; Nurdjali, Bachrun; Prayogo, Hari (Universitas Tanjungpura, 2016)
This research aims to count the number of individuals and the number of groups of proboscis monkey (Nasalis larvatus, Wurmb). Before determining the location of the research, first, field orientation was conducted. The transects were placed purposively as many as 6 transects at locations determined to be a place or habitat of proboscis monkey according to the results of orientation, and the implementation used the river survey method (JCM Sha, et al., 2008). The data collected were entered into the table and then the number of individuals and the number of population groups were counted. Prediction was made on density of individual/ha and density of group/ha. The results of data analysis showed that at a 95% confidence interval of individual density of proboscis monkey population lies between 0.50 to 2.82 individuals/ha, with a density of population groups lying between 0.09 to 0.26 group/Ha. For the 99% confidence interval of individual density of proboscis monkey population, it lies between -0.27 / ha to 3.59 individuals/ha, with a density of population of group lying between 0.03 to 0.32 group/Ha. Keyword: proboscis monkey, river survey, number of population, number of groups.